Design Framework and SWOT Analysis at Telaga Pethcare As a Solution to the Spread of the Rabies Virus in Bali Province - Dewi, Shanti Alena; Wardhana, Bayu; Trisnawati, Erna (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
This research was conducted to know and analyze the social business canvas model design framework for the Telaga Telaga Pethcare social enterprise. The social business model canvas framework is used to see and assess how impactful this social enterprise is on the social problems solved by Telaga Telaga Pethcare. This framework is a modification of the business model canvas framework which was previously widely used to design business concepts to be implemented. The social problem that Telaga Telaga Pethcare is trying to overcome and resolve is the problem of rabies which is currently a serious problem in Bali Province. The data collected reports that currently the number of rabies transmission cases in Bali has reached 14,827 cases. The research method used in this research uses descriptive qualitative methods. Data were collected using three methods, namely in-depth interviews, focus group discussions, and documentation. The selection of informants in this research used a purposive sampling technique. The research results in this study show that rabies cases are a concern for the Bali Provincial Government and the community. Telaga Telaga Pethcare is one of the pet shops in Bali Province where one of the social activities is providing animal care. To make it easier to analyze the social business of Telaga Telaga Pethcare, we use the social business canvas model. Meanwhile, to analyze weaknesses, strengths, opportunities, and challenges using SWOT analysis.